(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article outlines the procedures involved in an edge detection system in particular. The review details the fundamental concepts of edge detection, from the choice of the detection method to the differentiation and to the reason why a particular derivative is used. In edge detection many researchers hold on scientific work to enhance clearness and accurateness in order to be efficient foundation in face recognition, license plate detection and others. There are many existing edge detection methods like Canny, Sobel, Arbelaz and others are considered.